The Effect of Transformational Leadership and Work Motivation on Innovative Behavior - Tavip Purnomo Hadi; Burhanuddin Tola; Ma'ruf Akbar (IJHCM (International Journal of Human Capital Management), 2019)
This research is entitled "The Effect of Transformational Leadership and Work Motivation towards the Innovative Behavior". This research aims to determine the direct and indirect effects of transformational leadership work motivation on innovative behavior. The research approach is a quantitative method with path analysis. The population of this research is the medical representative from 3 pharmaceutical companies, taken proportionally in the Greater Jakarta Area of each company, namely: PT. X 40 people, PT. Y 40 people and PT. Z 30 people, with an affordable population of 110 people. The sampling technique was Simple Random Sampling through Krejcie and Morgan Tables, so that a representative sample of 86 respondents was obtained. Data collection was carried out through a Likert model structured questionnaire of the independent and dependent variables. The next step is to test the validity with Pearson Product Moment test analysis and reliability test with Cronbach Alpha test. Then the data analysis is performed as a statistical test requirement, namely; error normality test with Liliefors, homogeneity test and significance and linearity regression coefficient test. Found several conclusions, as follows; first, there is a direct effect of Transformational Leadership on Work Motivation, which means that transformational leadership styles can increase work motivation; second, there is a direct effect of Transformational Leadership on Innovative Behavior, which means that transformational leadership styles can enhance innovative behavior; third, there is a direct influence of Work Motivation on Innovative Behavior, which means work motivation can enhance innovative behavior; fourth, there is an indirect effect of Transformational Leadership on Innovative Behavior through Work Motivation, which means that transformational leadership styles can indirectly enhance innovative behavior through work motivation